Kids communicating climate change: learning from the visual language of the SchoolStrike4Climate protests. Issue 1 (2nd January 2023) - Catanzaro, Michelle; Collin, Philippa
ABSTRACT: Since 2018, school students around the world have gone on strike from school to call on leaders to take decisive action on climate change. Prominent in the resultant rallies are placards created by participants – from small children to their adult allies. This paper explores how students in the movement enact and activate visual approaches to communicating their concerns regarding climate change. By analysing the signage created by protestors at the largest yet rally held in Sydney, in September 2019, we situate the protests as a unique space for students' political voice. Our analysis of the signs and placards held by children finds that students use creative, mixed-media construction methods and draw on culturally significant objects and images to produce and visually communicate perspectives on climate change. This study shows how placards leverage emotional responses of anger, amusement and empathy to reflect the political, social and environmental dimensions of climate change, and collective demands for urgent policy action. In doing this, we highlight the role of visual communication in public protests and civic discourse, and the potential benefits to education on climate change. The visual language of the protest reinforces the critical or immediate nature of climate change to students as they draw on temporal symbols to communicate how they relate to climate change. We argue that these findings highlight the importance of creative, participatory and visual methods for student learning – and co-creating climate change education.